2007
DOI: 10.1007/s11069-006-9066-1
|View full text |Cite
|
Sign up to set email alerts
|

The 1780 seismic sequence in NE Sicily (Italy): shifting an underestimated and mislocated earthquake to a seismically low rate zone

Abstract: The southernmost sector of the Italian peninsula is crossed by an almost continuous seismogenic belt capable of producing M~7 earthquakes and extending from the Calabrian Arc, through the Messina Straits, as far as Southeastern Sicily. Though large earthquakes occurring in this region during the last millennium are fairly well known from the historical point of view and seismic catalogues may be considered complete for destructive and badly damaging events (IX £ I o £ XI MCS), the knowledge and seismic complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The 1823 earthquake near Cefalù, for instance, may have occurred off Cefalù along the south‐Tyrrhenian contractional seismic belt (Figure 1) with a magnitude greater than that hypothesized solely on the basis of the macroseismic evidence observed in the Cefalù area [ Guidoboni et al , 2003; Jenny et al , 2006]. However, even considering possible underestimates of historical earthquake magnitudes and their mislocations, it is widely accepted that in the last millennium there should be no gaps of information on destructive earthquakes in Sicily, especially for earthquakes occurring onshore [ Neri et al , 2006; Azzaro et al , 2007]. In synthesis, the above‐reported data and notions suggest that the occurrence of destructive earthquakes of magnitude over 6.4 in the Cefalù‐Etna seismic zone can be excluded since at least 1300 A.D. and, plausibly, since 1000 A.D. (http://zonesismiche.mi.ingv.it/).…”
Section: Seismological Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The 1823 earthquake near Cefalù, for instance, may have occurred off Cefalù along the south‐Tyrrhenian contractional seismic belt (Figure 1) with a magnitude greater than that hypothesized solely on the basis of the macroseismic evidence observed in the Cefalù area [ Guidoboni et al , 2003; Jenny et al , 2006]. However, even considering possible underestimates of historical earthquake magnitudes and their mislocations, it is widely accepted that in the last millennium there should be no gaps of information on destructive earthquakes in Sicily, especially for earthquakes occurring onshore [ Neri et al , 2006; Azzaro et al , 2007]. In synthesis, the above‐reported data and notions suggest that the occurrence of destructive earthquakes of magnitude over 6.4 in the Cefalù‐Etna seismic zone can be excluded since at least 1300 A.D. and, plausibly, since 1000 A.D. (http://zonesismiche.mi.ingv.it/).…”
Section: Seismological Datamentioning
confidence: 99%
“…Moreover, the time window of instrumental seismicity (i.e., 1981-2007) may be too short to show all seismic structures and their entire length. This problem is only partially solved by the historical analysis (Figure 8a), whose limitations are discussed above and in the specific literature [e.g., Guidoboni et al, 2003;Azzaro et al, 2007]. The above-discussed uncertainties concerning the instrumental and historical seismicity affect the seismic potential analysis (Table 1), whose results should, therefore, be regarded as a preliminary estimate.…”
Section: Geometry Kinematics and Seismic Potentialmentioning
confidence: 99%
“…Italian historical bibliography offers numerous accounts describing seismo-induced effects (Working Group CPTI04, 2004). The column Rt reports the source of the macroseismic observations: CFTI (Boschi et al, 2000); DOM (Monachesi and Stucchi, 1997) and Azz* refers to Azzaro et al (2007) which are reported in catalogues (Berardi et al, 1991;Galli and Ferreli, 1995;Romeo and Delfino, 1997;Boschi et al, 2000;Galli, 2000;Prestininzi and Romeo, 2000); these have also been used to draw maps of liquefaction-prone areas of Italy (Galli and Meloni, 1993) and, at local scale, of historical liquefaction-induced phenomena in the Catania area (Azzaro, 1999). This paper presents an updated dataset of liquefaction phenomena in central-eastern Sicily, realized through the revision of historical accounts, retrieved from the aforementioned catalogues and through an original research of historical primary sources.…”
Section: The New Dataset Of Historical Liquefaction Phenomena In Central-eastern Sicilymentioning
confidence: 99%
“…Since its formulation, the new EMS-98 scale has become more frequently used in Italy, although only after some initial perplexities (Molin, 1995;Tertulliani, 1995). This scale has been applied to a variety of cases, many of which have also included systematic comparisons with the MCS scale, which focuses on both the collection and interpretation of data collected in the field (Azzaro and Barbano, 1995;Azzaro et al, , 2004Azzaro et al, , 2006, and the analysis and revision of historical sources, also in terms of seismic histories and damage scenarios for hazard purposes (Azzaro et al, , 2007Barbano et al, , 2005. These 1997/98 earthquakes represent an important moment in the aforementioned process, since it was the first experimental «laboratory» involving a large group of Italian operators working in macroseismology.…”
Section: Discussionmentioning
confidence: 99%